Rupture of the myocardium in autopsied MI hearts - Monteiro,Valesca Bizinoto (2017)
Summary Although myocardial rupture occurs in only 2% to 4% of cases of acute myocardial infarction (AMI), there is a high mortality rate due to acute cardiogenic shock. We present the anatomopathological findings of three cases of myocardial rupture in autopsied hearts in the last 30 years, with a diagnosis of cardiac rupture in acute myocardial infarction. In these 30 years the percentage of AMI with myocardial rupture was 0.2%. Risk factors for post-AMI myocardial rupture include older age, atherosclerosis, diabetes mellitus and systemic arterial hypertension.